Birdshot Chorioretinopathy: Resistant versus Responsive. (16th March 2023) - Maleki, Arash; Look-Why, Sydney; Manhapra, Ambika; Asgari, Soheila; Garcia, Cristina M.; Al-Dabbagh, Alaa; Tsang, Catherine; Chang, Peter Y.; Anesi, Stephen D.; Foster, C. Stephen
ABSTRACT: Purpose: To search findings that can explain the heterogeneity between Resistant and Responsive patients with birdshot chorioretinopathy. Patients and Methods: This was a retrospective observational case series on "Responsive" versus "Resistant" birdshot chorioretinopathy Results: One-hundred-eighty and Ninety-nine patients were included in the Responsive and Resistant groups respectively. Multivariate analysis of paraclinical variables at the first visit demonstrated that mean deviation (p = .04), pattern standard deviation (p < .001), optic nerve head leakage (p = .012), large vessel leakage and staining (p = .01), and macular small vessel leakage (p = .03) were statistically significantly different between the two groups; however, at the visit preceding successful therapy, only macular small vessel leakage (p = .01) was statistically significantly different between the two groups Conclusion: .Small vessel leakage in the macular area and/or optic nerve head leakage at the earliest visit might be risk factors for resistant birdshot chorioretinopathy.